Faith-Based Charitable Giving and Its Impact on Notions of “Community”: The Case of American Muslim NGOs - Khan, Sabithulla (Qualitative Sociology Review, 2015)
With the current economic downturn, increased levels of unemployment, and poverty, the role of non-profits has come into spotlight. Considering that there are over 1.5 million NGOs in the U.S.A., and a proliferation of faith-based organizations (FBOs), their role in social capital, civic engagement cannot be discounted (Salamon, Sokolowski, and Anheier 2000). The role of FBOs has also been recognized as being important, and this became a part of mainstream discourse with the Charitable Choice provisions introduced by President Bill Clinton and consolidated under George W. Bush. While there is a lot of literature on Christian FBOs, there is very little written matter on American Muslim NGOs, or comparative research. American Muslim FBOs have emerged in the last 20 years, as important players in both domestic and international humanitarian aid movement. I will examine the case of Muslim faith-based giving to organizations to analyze how charitable giving towards them is influencing discourse about the American Muslim “community,” and how it is best to understand their work “relationally” rather than in opposition to other faith traditions (GhaneaBassiri 2010). While the narrative of giving among American Muslims seems simple and there is also very little literature on this issue, my preliminary research points towards a complicated landscape of giving, which combines both local giving at the mosque level and giving at the international level to the Ummah (community) or brotherhood, through transnational humanitarian aid agencies such as Islamic Relief. I argue that giving practices are creating new forms of “relational communities” in America. This notion of “relationality” can be applied in philanthropy, and is evident in the global humanitarian aid movement, as I demonstrate. I ask whether this is forming a new “moral geography” that is more pluralistic and broader than the one that we are familiar, especially in the American context. A closer examination of this phenomenon offers us insights into how a community is imagined and created. This paper seeks to contribute to the growing body of literature on FBOs, and also that on American philanthropy.